2022
DOI: 10.1038/s41385-022-00534-7
|View full text |Cite
|
Sign up to set email alerts
|

A single-cell lung atlas of complement genes identifies the mesothelium and epithelium as prominent sources of extrahepatic complement proteins

Abstract: To understand functional duality of the complement system in host defense and lung injury, a more comprehensive view of its localized production in the lung, and the impact of age on complement production are essential. Here, we explored the expression of complement genes through computational analysis of preexisting single cell RNA sequencing data from lung transcriptomes of healthy young (3 months) and old C57BL/6 mice (24 months), and humans. We characterized the distribution of 48 complement genes. Across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 59 publications
4
23
0
Order By: Relevance
“…For example, C3 expression by synovial fibroblasts has been linked to inflammation-mediated tissue priming in arthritis 28 . Furthermore, analogous to what we have shown here for IM muscle, different complement genes are differentially expressed by different cells of the lung 29 . Specifically, lung macrophages express C1QA, C1QB, and C1QC, whereas lung mesothelial cells and fibroblasts expressed C1R, C1S, and C3 29 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…For example, C3 expression by synovial fibroblasts has been linked to inflammation-mediated tissue priming in arthritis 28 . Furthermore, analogous to what we have shown here for IM muscle, different complement genes are differentially expressed by different cells of the lung 29 . Specifically, lung macrophages express C1QA, C1QB, and C1QC, whereas lung mesothelial cells and fibroblasts expressed C1R, C1S, and C3 29 .…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, analogous to what we have shown here for IM muscle, different complement genes are differentially expressed by different cells of the lung 29 . Specifically, lung macrophages express C1QA, C1QB, and C1QC, whereas lung mesothelial cells and fibroblasts expressed C1R, C1S, and C3 29 . Taken together, these findings suggest that the coordinated local expression of complement genes is not specific to muscle tissue in IM but, rather, may be a general mechanism to regulate the complement pathway in inflamed tissues.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, although we have focused on FB in lung epithelial cells, other complement components have also been shown to modulate lung epithelial cell responses. For example, airway epithelial cells and alveolar (type 1 and type 2) epithelial cells also express C3aR, C5, C5aR1, and C5aR2, in addition to C3 and FB ( 22 , 56 , 57 ). C3aR activation on alveolar type 2 epithelial cells has recently been implicated in promoting endoplasmic reticulum stress and exacerbating bleomycin-induced lung injury, cellular apoptosis, and inflammation, which was suppressed by decay-accelerating factor (CD55) induction, a membrane-associated complement regulator ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the protective effects of C3 have largely been attributed to it being sourced from the liver and present in a high concentration in the circulation. However, we and others have previously demonstrated that C3 is also produced outside the liver by multiple immune and nonimmune cell populations (17)(18)(19)(20)(21)(22). This observation has implications, especially for organs that constantly interact with pathogens and environmental toxins, such as the lung (6,23).…”
Section: Introductionmentioning
confidence: 90%
“…In human lung, intracellular C3 protects airway epithelial cells from nutrient deprivation-induced cell death via a currently unknown mechanism 85 . C5 expression has also been observed in healthy human and mouse type II alveolar epithelial cells; however, its functional relevance has not yet been explored 86 . In bladder epithelial cells, the processed CYT-2 domain of CD46 controls hypoxia-inducible factor 1α (HIF1α) and is associated with malignant transformation and bladder cancer, probably via hyperactivation of MYC-mediated cell proliferation 45 .…”
Section: Non-immune Cells and Tissuesmentioning
confidence: 99%